Tax financing options for new social protection instruments: The equity implications of taxing more to expand the South African social security system - Maya Goldman; Ntuthuko Hlela (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
In this paper, we use a static fiscal incidence analysis model to evaluate the poverty and inequality impacts of using fiscal policy to finance expanded social spending in South Africa. We assess three methods to enhance the social protection system's equity objectives: increasing the size and/or coverage of the existing Social Relief of Distress grant and introducing a universal or working-age basic income grant. The implications of financing these reforms are examined using four tax instruments: increasing the value-added tax rate, increasing personal income tax rates, reducing the personal income tax primary annual rebate, and introducing a surcharge on incomes. While we discuss behavioural effects, they are not included in the model. Our analysis indicates that an expansion of the social security system financed through increased taxation could substantially reduce poverty and inequality to varying degrees depending on the taxes and transfers used.
Keywords: H22; I38; D31; 330; fiscal policy; fiscal incidence; social spending; inequality; poverty; taxes; transfers